2018
DOI: 10.1002/hbm.24308
|View full text |Cite
|
Sign up to set email alerts
|

Structural network topology correlates of microstructural brain dysmaturation in term infants with congenital heart disease

Abstract: Neonates with complex congenital heart disease (CHD) demonstrate microstructural brain dysmaturation, but the relationship with structural network topology is unknown. We performed diffusion tensor imaging (DTI) in term neonates with CHD preoperatively (N = 61) and postoperatively (N = 50) compared with healthy term controls (N = 91). We used network topology (graph) analyses incorporating different weighted and unweighted approaches and subject-specific white matter segmentation to investigate structural topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 71 publications
(172 reference statements)
2
41
2
Order By: Relevance
“…They can be summarized as a pattern of reduced integration and increased segregation. Similar findings of a perturbated network architecture in CHD neonates compared to controls were reported by Schmithorst et al (Schmithorst et al 2018). In their study CHD neonates underwent either pre-or postoperative MRI.…”
Section: Reduced Integration and Higher Segregation Of Global And Nodsupporting
confidence: 79%
See 2 more Smart Citations
“…They can be summarized as a pattern of reduced integration and increased segregation. Similar findings of a perturbated network architecture in CHD neonates compared to controls were reported by Schmithorst et al (Schmithorst et al 2018). In their study CHD neonates underwent either pre-or postoperative MRI.…”
Section: Reduced Integration and Higher Segregation Of Global And Nodsupporting
confidence: 79%
“…Furthermore, we were able to reveal perturbations in network segregation. In contrast to our analysis, CHD neonates with any type of brain injury were excluded in Schmithorst et al (Schmithorst et al 2018). We assume that our results are more representative of network disturbances found in CHD neonates as perioperative brain injury, such as punctate WMI and focal stroke, are common in CHD (Peyvandi et al 2019).…”
Section: Reduced Integration and Higher Segregation Of Global And Nodmentioning
confidence: 91%
See 1 more Smart Citation
“…local) connectivity is disrupted ( Fischi-Gomez et al, 2016 , Karolis et al, 2016 , Batalle et al, 2017 , Ball et al, 2014 ). In neonates with CHD, recent studies have demonstrated reduced functional connectivity ( De Asis-Cruz et al, 2018 ) and alterations in structural network topology pre-operatively ( Schmithorst et al, 2018 ). However, it is not clear whether altered structural network topology in infants with CHD prior to surgery can be explained by disruptions to core-peripheral connections.…”
Section: Introductionmentioning
confidence: 99%
“…3 Indeed, it is now understood that brain development within the context of critical CHD (i.e., CHDs requiring intensive surgical intervention(s) to sustain life) is often atypical, with signs of deviation from expected neuronal maturation and volumetric trajectories recognisable as early as the late-second/early-third prenatal trimester [4][5][6][7][8] and evidence of structural, functional, and network topological brain abnormalities documented throughout adolescence and young adulthood. [9][10][11][12][13][14][15][16][17][18][19][20] Children and adolescents with critical CHD are also at heightened risk for a range of neurobehavioural and psychosocial challenges, 21 most notably in executive function. [22][23][24][25] Executive function is an umbrella term, encompassing three core components: inhibitory control, working memory, and cognitive flexibility.…”
mentioning
confidence: 99%